BRAND POSITIONING DAN PERCEPTUAL MAPPING UNIVERSITAS BUNDA MULIA, ATMA JAYA, BINUS, IBII, DAN UNTAR DENGAN METODE DISCRIMINANT ANALYSIS - Rudy Santosa Sudirga (Universitas Bunda Mulia, 2017)
Although universities are increasingly competing for accepting huge number of students, little has been written about the influence of cultural values on the brand positioning of university education brands. This study investigates the values of brand positioning for some private university education, and the factors teh students use to gain information about universities. The purpose of this paper is to present a call to action for universities to practice what they preach in developing and communicating differentiated brands. The paper reviews some recent literature on university brand positioning strategy. Universities marketing manager should seek to clearly differentiate their offering from the competition. The large amounts of expenditure on university marketing would be more efficiently used if the principles of brand management taught within them were applied properly. The public perception of a university’s programs is often considered a primay factor in building the brand positioning of the respevtive institution. Maintaining a favorable brand positioning can have a significant impact when recruiting potential students, when soliciting corporate partners, and when facilitating development opportunities with alumni and key stakeholders. This study also aims to discuss how the attributes of university brands influence consumers’ evaluations of brand positioning and the differences and competition among brands. A perceptual map, developed using probabilistic discriminant analysis algorithms, depicts the relative position of each brand and illustrates their attractive properties.This statistical techniques can enhance managers’ ability to identify promising brand positions and enhance the overall brand positioning design process. A brand’s positioning is designed to develop a sustainable competitive advantage on product attribute (s) in the consumer’s mind. Brand positioning has been defined as the act of designing the image of the firm’s offering so that target customers understand and appreciate what the product stands for in relation to its competitors. Each brand within a set of competitive offerings is thought of as occupying a certain position in a customer’s “perceptual space”. Perceptual mapping refers generally to techniques used to represent and evaluate a brand’s positioning.Key Words- Brand Positioning, Perceptual Mapping, Universities